2022
DOI: 10.1136/bjsports-2022-106312
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and burden of illness at the Tokyo 2020 Paralympic Games held during the COVID-19 pandemic: a prospective cohort study of 66 045 athlete days

Abstract: ObjectiveTo describe the incidence and burden of illness at the Tokyo 2020 Paralympic Games, which was organised with strict COVID-19 countermeasures.MethodsDaily illnesses were recorded via the web-based injury and illness surveillance system (teams with their own medical staff; n=81), and local polyclinic services (teams without their own medical staff; n=81). Illness proportion, incidence and burden were reported for all illnesses and in subgroups by sex, age, competition period, sports and physiological sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Team sizes were determined by using the final master list of participating athletes in each team published by the IPC prior to the Games. The calculation of athlete days (total, precompetition and competition periods), injury proportion (IP) and incidence is consistent with the methodology of previous iterations of the Paralympic Injury and Illness Surveillance Studies and presented in supplementary file 2 2–6 17 18…”
Section: Methodsmentioning
confidence: 77%
“…Team sizes were determined by using the final master list of participating athletes in each team published by the IPC prior to the Games. The calculation of athlete days (total, precompetition and competition periods), injury proportion (IP) and incidence is consistent with the methodology of previous iterations of the Paralympic Injury and Illness Surveillance Studies and presented in supplementary file 2 2–6 17 18…”
Section: Methodsmentioning
confidence: 77%
“…Dermon et al 17 reported a higher incidence of heat-related illnesses in wheelchair athletes than in able-bodied athletes due to altered vasomotor control, large trunk area, proximity to the ground, high radiant heat and impaired body temperature control in disabled sports. Furthermore, the risk of heat-related illnesses is high both indoors and outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…The following items were examined: (1) date, (2) venue, (3) event name, (4) time of occurrence, (5) continent of origin, (6) gender, (7) years by decade, (8) chief problem, (9) physician diagnosis, (10) severity classification, (11) vital signs at the initial visit, (12) treatment, (13) transportation methods (ambulance, other), (14) admissions to the medical facility, (15) transport to medical facilities, (16) whether transported to a medical facility, (17) hospitalisation and treatment at medical facilities, (18) outcome and (19) WBGT at the venue.…”
Section: Examination Itemsmentioning
confidence: 99%
“…On the other hand, studies in well-trained able-bodied athletes have shown that high T c values are common, well tolerated (i.e., no health complaints), and not strongly associated with performance loss (2–4). Data on EHI in para-athletes remain scarce, but the available studies suggest that para-athletes are not predisposed to an elevated EHI risk per se (5–7). During the Tokyo 2020 Paralympic and Olympic Games, only 0.4% of para-athletes and 0.7% of able-bodied athletes reported to medical services with (exertional) hyperthermia or heat illness (7,8).…”
mentioning
confidence: 99%
“…Data on EHI in para-athletes remain scarce, but the available studies suggest that para-athletes are not predisposed to an elevated EHI risk per se (5–7). During the Tokyo 2020 Paralympic and Olympic Games, only 0.4% of para-athletes and 0.7% of able-bodied athletes reported to medical services with (exertional) hyperthermia or heat illness (7,8). In most cases, the illness did not affect subsequent training or competition availability, suggesting that illnesses were mild.…”
mentioning
confidence: 99%